Searching for the role of emotions in e-learning. (December 2020) - Mayer, Richard E.
Abstract: This special issue of Learning and Instruction examines the role of emotions in academic learning, with a special focus on emotions in computer-supported academic learning (or e-learning). Three central research challenges concerning emotion in e-learning are: identification (e.g., what are the key emotions in e-learning?), measurement (e.g., how can we tell how strongly a learner is experiencing each key emotion during e-learning?), and explanation (e.g., what are the causes and consequences of the learner's emotional state during learning?). A useful goal of research on emotions in e-learning is to test an affective-cognitive model of e-learning with links among an e-learning episode, the learner's emotional reaction during learning, the learner's cognitive processing during learning, and the learning outcome. Highlights: This special issue examines emotions in computer-supported academic learning. What are the key emotions in e-learning? How can we tell how strongly learners experience key emotions in e-learning? What are the causes and consequences of the learner's emotional state? A goal is to test an affective-cognitive model of e-learning.